2022
DOI: 10.1007/s11695-022-06232-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Endoscopic Sleeve Gastroplasty in the Elder Population

Abstract: Purpose With the aging of the population and the epidemic spread of obesity, the frequency of older individuals with obesity is steadily growing. To date, no data evaluating the use of endoscopic sleeve gastroplasty (ESG) in the elderly have been published. In this case series, we evaluate the short- and medium-term outcomes of ESG in patients with obesity aged 65 years and older. Materials and Methods A retrospective analysis was done on a prospective dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…However, our analysis suggests that the initial stages witness greater weight loss among the younger population, while a largely similar trend emerges between younger and older patients in the long run. This evidence confirms what was reported in a previous study, supporting the use of ESG as a valid therapeutic strategy also in elder patients with obesity [30].…”
Section: Discussionsupporting
confidence: 92%
“…However, our analysis suggests that the initial stages witness greater weight loss among the younger population, while a largely similar trend emerges between younger and older patients in the long run. This evidence confirms what was reported in a previous study, supporting the use of ESG as a valid therapeutic strategy also in elder patients with obesity [30].…”
Section: Discussionsupporting
confidence: 92%
“…In the study conducted by Nielsen et al, female gender was shown to result in greater weight loss post-surgery, whereas in the study by Matteo et al, it was demonstrated that gender had no effect on the success of the surgery. [21,22] In our study, we also found that gender did not have any significant impact on postoperative weight loss. The impact of age on postoperative weight loss also yields varying results in studies.…”
Section: Discussionsupporting
confidence: 59%
“…The efficacy of ESG has been examined by multiple non‐randomized studies and a randomized study 5,10,24,29,40 . The recently published MERIT trial proved the superiority of ESG compared with lifestyle modifications alone for weight loss 29 .…”
Section: Safety and Efficacymentioning
confidence: 99%